Analisis Pengembangan Produk Ekspor Woven Earth Craft - Ais Mariya Ulva; R. Yuniardi Rusdianto (Jurnal Riset dan Inovasi Manajemen, 2024)
Exports are goods and services produced in one country and sold to buyers in another country. The biggest contributing factor to Gross Domestic Product is exports. "Woven Earth Craft" products are handicrafts made by hand using natural materials, such as soil or natural fibers, and formed through woven techniques. The purpose of this research is to find out how to develop Woven Earth Craft export products. The research method used is qualitative research method. The development carried out is branding, using appropriate packaging, using digital marketing strategies and completing export documents. With this, the steps taken by Woven Earth Craft are first planning, adjusting and testing international markets. This export development provides deep insight into the importance of product development as a foundation for meeting consumer demands and achieving business growth. By doing this development Woven Earth Craft is able to compete in the international market.